Iron increases the susceptibility of colorectal cancer cells to compound Kushen Injection via the decrease of TOP2A and p53 - Xingkang Wu; Chenchen Han; Lu Wang; Xuemei Qin (Elsevier, 2022)
Background: Colorectal cancer (CRC) is one type of worldwide refractory tumors with high morbidity and mortality. Iron is responsible for the development and progression of CRC. Whereas, iron-deficiency anemia is a common comorbidity and a major cause of tumor aggressiveness in CRC patients. Thus, there is a high demand for the therapeutic strategy of iron deficiency anemia for iron therapy without tumor promotion in CRC patients. Methods: Sulforhodamine B (SRB) assay was applied to evaluate in vitro antitumor activity, microscopical examination, and 3D spheroid culture were used to detect the effect of drugs on cell morphology and cell growth. Differentially labeled live and dead cells were detected by Calcein-AM/PI double fluorescent staining method, EdU staining assay was performed to evaluate cell proliferation. Network pharmacology and western blotting were carried out to dissect the potential key genes involved in the synergetic anti-CRC activity of drug combinations. And small-molecule modulators of proteins were employed to confirm the roles of potential key genes in cooperativity between two combined drugs. Results: Iron supplements, including FeSO4 and ferric ammonium citrate (FAC), increased the in vitro antitumor activity of Compound Kushen Injection (CKI) against SW480 and HCT116 CRC cells. CKI and FAC combination specifically inhibited cell proliferation but not induced cell death in SW480 cells. Mechanistically, FAC decreased the protein expression of TOP2A, and CKI reduced the levels of p53 protein, therefore inhibiting the proliferation of SW480 cells. Conclusion: This article demonstrated that iron and CKI synergistically inhibited the cell proliferation of CRC cells by individually reducing the expression of TOP2A and p53. This article will open a new avenue for the treatment of iron-deficiency CRC.